2018
DOI: 10.1039/c8sm01025k
|View full text |Cite
|
Sign up to set email alerts
|

A critical and quantitative review of the stratification of particles during the drying of colloidal films

Abstract: For a wide range of applications, films are deposited from colloidal particles suspended in a volatile liquid. There is burgeoning interest in stratifying colloidal particles into separate layers within the final dry film to impart properties at the surface different to the interior. Here, we outline the mechanisms by which colloidal mixtures can stratify during the drying process. The problem is considered here as a three-way competition between evaporation of the continuous liquid, sedimentation of particles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
101
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(104 citation statements)
references
References 106 publications
3
101
0
Order By: Relevance
“…Therefore, drying colloidal suspensions with a binary size distribution has attracted much attention for a decade. 9 One of the most attractive issues is the segregation or stratication phenomenon of small or large particles that occurs during drying. [10][11][12][13] Sun et al 14 investigated drying of a sessile droplet of a binary suspension.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, drying colloidal suspensions with a binary size distribution has attracted much attention for a decade. 9 One of the most attractive issues is the segregation or stratication phenomenon of small or large particles that occurs during drying. [10][11][12][13] Sun et al 14 investigated drying of a sessile droplet of a binary suspension.…”
Section: Introductionmentioning
confidence: 99%
“…Pé helps to determine the dominant process (evaporation or diffusion) during the film formation process. 17,32,33 The diffusion coefficient (D) of a particle is given by D = k B T/(6ZpR), where k B is the Boltzmann constant, T is the absolute temperature, R is the radius of the particle and Z is the viscosity of the solvent. Hence the Péclet number can be depicted as expressed in eqn (1).…”
Section: Effect Of Surface Chemistry Of Silica On Film Forming Behaviormentioning
confidence: 99%
“…16 Furthermore, the experimental results were correlated with simulation and modeling of stratified films and it was concluded that higher particle size ratio favors stratification in dilute colloidal dispersions. 17 Similarly, Zhou et al has showed that stratification was favored by high particle size ratio and high Péclet number, 18 i.e. the ratio between mass transport by convection flow and diffusion of the particles.…”
Section: Introductionmentioning
confidence: 96%
“…The difference in diffusion rate for particles of different sizes will lead to a different amount of accumulation at the drying front. [25][26][27][28][29] The Peclet number, the ratio of the evaporation rate against the diffusion rate, is often used to quantify and predict the stratification behaviour. However, the Peclet number does not consider the surface adsorption of particles at all.…”
Section: Introductionmentioning
confidence: 99%